2019
DOI: 10.18203/2320-6012.ijrms20185504
|View full text |Cite
|
Sign up to set email alerts
|

Role of CT enterography in evaluation of small bowel disorders

Abstract: Background: Small bowel pathologies are an enigma for clinicians and difficult to assess and evaluate for clinicians. In order to establish the efficacy of MDCT Enterography in diagnostic characterisation of small bowel lesions, the current study was undertaken.Methods: A prospective observational cross-sectional study was carried out in a tertiary care hospital. 30 patients with clinically suspected small bowel disease underwent CT enterography using iso-osmotic mannitol as neutral enteral contrast. CT entero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Bowel thickness and mucosal hyperenhancement were the most frequently seen CTE results in the current investigation, occurring in 25 (62.5 %) and 20 (50 %) patients, respectively. Results are in line with earlier research [ 10 ]. It was determined that intestinal diseases might affect the jejunum, ileum, or other colonic segments separately or in various combinations.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Bowel thickness and mucosal hyperenhancement were the most frequently seen CTE results in the current investigation, occurring in 25 (62.5 %) and 20 (50 %) patients, respectively. Results are in line with earlier research [ 10 ]. It was determined that intestinal diseases might affect the jejunum, ileum, or other colonic segments separately or in various combinations.…”
Section: Discussionsupporting
confidence: 93%
“…With three cases (7.5%) of neoplastic adenocarcinoma, nonneoplastic causes accounted for the majority of mural thickening (91.3%). Our results align with those of earlier researches [10][11][12].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Revision of their histopathological records revealed one IBD, one FMF, one celiac disease, and two neoplastic lesions confirmed to be GIST. This is compared to a study by Misra et al who reported a sensitivity and specificity of MDCTE to be 95.83% and 100% respectively with accuracy of 96.66% in diagnosis of small bowel diseases [16].…”
Section: Discussionmentioning
confidence: 69%
“…9 The small bowel distension was graded 0-3 (grade 0 was for no distension, while grade 3 was for optimal distension) by grading on the basis of diameters of ileum and jejunum. 11 Poor distension was observed in only 2 of the 107 patients. Most of the causes for symmetric wall thickening along the circumference of the bowel were benign in etiology.…”
Section: Discussionmentioning
confidence: 95%